PROPAGATION OF TUNERA PLANTS - Febriana Roosmawati; Adi Widjajanto; Ritna Wahyuni; Dhany Fadlur Rohman; Aldi Krisdian; Dimas Bagus Setiawan; Bistok Gumartop; Bisma Agung; Ahmad Fauzi Pangaribuan (RADJA PUBLIKA, 2024)
The propagation of Tunera Plants with the aim and Community Service Program implemented is to synergize the potential and knowledge possessed by the Academic Community with the realities currently being faced by society, especially our community which is related to the competence of the field of knowledge of the Plantation Cultivation Study Program and Plantation Product Processing Technology Study Program. Benefits The benefit of the Community Service Program implemented is the creation of multiplication of tunera subulate plants among community farmers. It is hoped that this will be beneficial for farmers in controlling pests naturally without using pesticides which can reduce the fertility of the soil itself. Community service was carried out in Buntu Turunan Village, Hatonduhan District, Simalungun Regency, North Sumatra Province, carried out for 3 days, starting from 28 - 29 August 2023. With the results of community service activities, it can provide education and innovation for the community that the tunera plant is very important. useful for oil palm plants in controlling pests including fireworms.